Analysis Of Surface Runoff Potential At Medan Industrial Estate Use SCS Method - Yudha Hanova (Universitas Tidar, 2018)
Flood disaster at the region Medan Industrial Estate resulted the losses in infrastructure, farming, and residence. Flood discharge at Medan Industrial Estate are influenced by surface runoff from several catchment area in Medan Industrial Estate. Analysis of potential for surface runoff is expected to provide input and information to find alternative solutions appropriate flood mitigation. Discharge of surface runoff were analyzed using SCS method with the return period of 1, 2 and 5 Years. Rainfall data are obtained BMKG Stations of Maritim Belawan. Effective rainfall calculated using SCS-CN method on condition AMC III (wet conditions). The results of the analysis of the potential for surface runoff maximum for 1 year return period on DAS I, II, III, IV, V, and VI was 17.631 m3/s, 22.183 m3/s, 12.621 m3/s, 11.338 m3/s, 18.224 m3/st, dan 15.839 m3/s. To return period of 2 years was 31.234 m3/sec, 39.235 m3/s, 22.351 m3/det, 20.044 m3/det, 32.300 m3/det, dan 28.097 m3/det. For the return period of 5 years is 45.346 m3/s, 56.926 m3/s, 32.446 m3/s, 29.076 m3/s, 46.903 m3/s, dan 40.816 m3/s.